(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The scientific article provides a comprehensive approach to the system-structural interpretation of simple words and phrases, lexical-semantic and functional aspects, indicators of segregation, individual supernatural features and problems.